ANALISIS PENERAPAN TOTAL QUALITY SERVICE (TQS) TERHADAP CUSTOMER SATISFACTION PADA PT PEGADAIAN (PERSERO) CABANG PEKANBARU KOTA - Rahma, Ismiwiya; Samsir, Samsir; Marpaung, Rio Jonnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to test the variables of total quality service (reliability, responsiveness, assurance, empathy, tangibles) on customer satisfaction at PT Pegadaian (Persero) the Branch Office of Pekanbaru City. The object of this research is PT Pegadaian (Persero) the Branch Office of Pekanbaru City. The population in this study are customers of PT Pegadaian (Persero) the Branch Office of Pekanbaru City amounting to 51,134 customers with a sample of 100 customers. Primary data was collected by questionnaire as instrument to prove the result of research, to test the hypothesis in this study used Multiple Linear Regression method and SPSS program version 20. The sampling technique that has been selected is the probability sampling method with random sampling (simple random sampling). The results of this study indicate that all variables of TQS (reliability, responsiveness, assurance, empathy, tangibles) have significant influence on customer satisfaction at PT Pegadaian (Persero) Branch Pekanbaru City.Keywords : Total quality service, reliability, responsiveness, assurance, empathy, tangibles, customer satisfaction